A lipid profile study in polycystic ovary syndrome women - Prajapati, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Dyslipidemia in PCOS has multifactorial causation and insulin resistance plays a pivotal role by stimulation of lipolysis and altered lipases which are characterized by higher triglyceride and lower high-density lipoprotein cholesterol.1 Methods: This observational cross-sectional study was conducted in the obstetrics and gynaecology department of SPS hospital Ludhiana Punjab and included 60 women with PCOS and 30 non PCOS women of age group 18-40 who meet the inclusion criteria. Results: PCOS women with BMI <18.5 (underweight) their mean cholesterol, HDL, LDL, VLDL and triglycerides were 158.00, 48.00, 74.00, 35.60, 178.00 respectively. PCOS women with BMI ranging from >18.5-24.99 (normal) the mean±SD for cholesterol, HDL, LDL, VLDL and triglycerides were 169.50 ± 21.83, 44.86±2.66, 85.80±20.33, 38.84±3.57, 194.18±17.86 respectively. PCOS Subjects with BMI25-29.99 (overweight) Mean±SD for total cholesterol was 197.04±18.16, HDL=40.48±3.19, LDL=112.37±18.10, VLDL=44.20±2.89 and for triglycerides was 221.00±14.45. Conclusions: An early treatment for obesity should be a priority to prevent cardiometabolic complications in future in women with Polycystic ovaries syndrome.